Peripheral fibroma obstructing the eruption pathway - Prashanth Shetty; Vivek Padmanabhan; P R Kavitha; Harvey Thomas (Wolters Kluwer Medknow Publications, 2012)
Reactive hyperplasias comprise a group of fibrous connective tissue lesions that commonly occur in oral mucosa secondary to injury. Peripheral fibroma is also a type of reactive hyperplasia. Peripheral fibroma is a reactive hyperplastic mass that occurs on the gingiva and is derived from connective tissue of the submucosa or periodontal ligament. It may occur at any age, although it does have a predilection for young adults. Females develop these lesions more commonly than do males. Here, we are presenting a case report of a child who is 6 years old and presented to us with a swelling in the lower anterior region which was providing discomfort to the child and also was obstructing the eruption pathway of the permanent central incisor in the region. The lesion was surgically excised.